Dedication in nursing: A concept analysis - Raheleh Sabetsarvestani; Emine Geçkil; Zahra Hadian Shirazi (Kashan University of Medical Sciences, 2022)
Background: Dedication is one of the components of professional nursing. However, no clear consensus exists on the definition of dedication in nursing, and it is difficult to understand and operationalize this concept in clinical settings. Objectives: This study aimed to analyze the concept of dedication in nursing. Methods: This concept analysis was done using the hybrid model from February to June 2021. In the theoretical phase, the existing literature on dedication in nursing was reviewed in international databases of PubMed, Science Direct, ProQuest, Ovid, and Scopus. The keywords were "dedication" and "nursing". After excluding duplicate and irrelevant records, 34 documents were reviewed. In the field phase, semistructured interviews were conducted with six nurses to gather new qualitative data on their experiences of dedication. In the integration phase, the findings of the earlier phases combined to provide a comprehensive definition of the concept. Content analysis was used to analyze the data. Results: Dedication in nursing was defined as a feeling and state of mind and heart, like an untiring commitment that is the art and essence of nursing. It is caring from one's heart with all human beings and technical resources available, doing beyond regular work hours and organizational and legal duty. This act usually happens without expectation for any reward or incentives in such a way that may lead to neglecting one's own needs. Conclusion: This concept analysis can be a good guide for nurses, teachers, and managers to know the meaning of dedication and recognize how to breed the spirit of dedication in nursing and prevent its negative consequences.